Melatonin and pathological cell interactions: Mitochondrial glucose processing in cancer cells - Reiter, Russel J.; Sharma, Ramaswamy; Rosales-Corral, Sergio; Manucha, Walter; Chuffa, Luiz Gustavo de Almeida; Zuccari, Debora Aparecida Pires de Campos (MDPI, 2021)
Melatonin is synthesized in the pineal gland at night. Since melatonin is produced in the mitochondria of all other cells in a non-circadian manner, the amount synthesized by the pineal gland is less than 5% of the total. Melatonin produced in mitochondria influences glucose metabolism in all cells. Many pathological cells adopt aerobic glycolysis (Warburg effect) in which pyruvate is excluded from the mitochondria and remains in the cytosol where it is metabolized to lactate. The entrance of pyruvate into the mitochondria of healthy cells allows it to be irreversibly decarboxylated by pyruvate dehydrogenase (PDH) to acetyl coenzyme A (acetyl-CoA). The exclusion of pyruvate from the mitochondria in pathological cells prevents the generation of acetyl-CoA from pyruvate. This is relevant to mitochondrial melatonin production, as acetyl-CoA is a required co-substrate/co-factor for melatonin synthesis. When PDH is inhibited during aerobic glycolysis or during intracellular hypoxia, the deficiency of acetyl-CoA likely prevents mitochondrial melatonin synthesis. When cells experiencing aerobic glycolysis or hypoxia with a diminished level of acetyl-CoA are supplemented with melatonin or receive it from another endogenous source (pineal-derived), pathological cells convert to a more normal phenotype and support the transport of pyruvate into the mitochondria, thereby re-establishing a healthier mitochondrial metabolic physiology.
Keywords: Aerobic glycolysis; Cancer; Diseased cells; Melatonin; Mitochondrial metabolism; Warburg effect